Needs and targets for the multi sex combs gene product in Drosophila melanogaster. - Saget, O.; Forquignon, F.; Santamaria, P.; Randsholt, N.B. (Genetics, 1998)
We have analyzed the requirements for the multi sex combs (mxc) gene during development to gain further insight into the mechanisms and developmental processes that depend on the important trans-regulators forming the Polycomb group (PcG) in Drosophila melanogaster. mxc is allelic with the tumor suppressor locus lethal (1) malignant blood neoplasm (l(1)mbn). We show that the mxc product is dramatically needed in most tissues because its loss leads to cell death after a few divisions. mxc has also a strong maternal effect. We find that hypomorphic mxc mutations enhance other PcG gene mutant phenotypes and cause ectopic expression of homeotic genes, confirming that PcG products are cooperatively involved in repression of selector genes outside their normal expression domains. We also demonstrate that the mxc product is needed for imaginal head specification, through regulation of the ANT-C gene Deformed. Our analysis reveals that mxc is involved in the maternal control of early zygotic gap gene expression previously reported for some PcG genes and suggests that the mechanism of this early PcG function could be different from the PcG-mediated regulation of homeotic selector genes later in development. We discuss these data in view of the numerous functions of PcG genes during development.